(untitled) (UTM Press - Edited Book, 2023)
The edited book Copula Modelling and its Application addresses the development of the Copula definition in the modelling of rainfall data. The book begins with the construction of new copula families, to add into the list of the existing families that are widely discussed in the literature. The definitions of dependency are illustrated using few approaches and the derivation of copula functions using a mathematical statistical approach is focused. Several applications of the copula model are also demonstrated in this edited book